GHRELIN GENE POLYMORPHISM IN IRON DEFICIENCY ANEMIA - Bahadir, E.; Akarsu, S.; Etem, E. Onalan (Ferrata Storti Foundation, 2015)
[Abstract Not Available]
20th Congress of European-Hematology-Association -- JUN 11-14, 2015 -- Vienna, AUSTRIA